2009
DOI: 10.1159/000239626
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Solitary Bone Metastasis to the Tibia from Colorectal Cancer

Abstract: The onset of osseous metastases during the course of colorectal cancer is not common. When they appear they are usually combined with visceral metastases to the liver, lungs and brain. In our report we refer to the case of a 78-year-old patient who presented a solitary bone metastasis from rectal carcinoma in the middle of his right tibia. A year before he had been operated for a Dukes stage B1 adenocarcinoma of the rectum. The rest of the check was negative for other metastases. He received external radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…Chalkidou et al, reported a solitary tibial metastasis from rectal cancer 12 months after surgery. [7] In our case the metastasis was diagnosed 26 months after resection of the tumor. Survival after bone metastasis is very poor, with a median time of 5 months when associated with visceral metastasis also.…”
Section: Discussionmentioning
confidence: 55%
“…Chalkidou et al, reported a solitary tibial metastasis from rectal cancer 12 months after surgery. [7] In our case the metastasis was diagnosed 26 months after resection of the tumor. Survival after bone metastasis is very poor, with a median time of 5 months when associated with visceral metastasis also.…”
Section: Discussionmentioning
confidence: 55%
“…Talbot et al [12] described a median time of 21 months and Chalkidou et al reported a solitary tibial metastasis from rectal cancer 12 months after surgery. [13] In our case the metastasis was diagnosed 13 years after resection of the tumour.…”
Section: Discussionmentioning
confidence: 57%
“…Skeletal metastases in patients with colorectal carcinoma are relatively uncommon with an incidence of 4.7-10.9% ( 2 ). A large retrospective study found an incidence of approximately 10% ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is one of the leading causes of cancer-related death worldwide ( 1 ). Skeletal metastases in patients with colon carcinoma are rare, and the occurrence of isolated an solitary skeletal metastasis in the absence of visceral metastases is even rarer ( 2 ). These metastases can have bizarre radiological appearances due to post-treatment changes.…”
Section: Introductionmentioning
confidence: 99%